Analisis Perilaku Konsumtif Penggunaan Aplikasi Shopee dalam Metode Pembayaran Shopeepay dan COD pada Mahasiswa Universitas Muhammadiyah Riau - Adelia, Vella; Helmilia, Nelsy; Azzahra, Naina; Azmi, Zul (CV. Kalimasada Group, 2023)
Shopee is one of the most popular online shopping platforms. Payment through ShopeePay is one of the non-cash payments that is quite often used. The purpose of this research is to analyze the consumptive behavior of using the Shopee application in the ShopeePay and COD payment methods for Muhammadiyah Riau University students. However, previous studies show that the COD payment method is more widely used than ShopeePay. This research uses a qualitative method with a descriptive analysis approach. The sample of this study were students who used the payment system through ShopeePay and COD at Muhammadiyah Riau University. The results of this study indicate that 95.5% use the Shopee application and 4.5% do not use the Shopee application, this is enough to show that the Shopee application is indeed very popular. In the payment method, the use of COD is 67.6%, this shows that COD is more widely used compared to the ShopeePay payment method which is only around 32.4%.